Using of blue green algae extract and salicylic acid to mitigate heat stress on roselle (Hibiscus sabdariffa L.) plant under Siwa Oasis conditions: - Hanafy, Yasser Adel; Mohemed Badawy, Moustafa Yehia; Hamed, Emad Saleh (Plant Science Today, 2022)
Increasing temperature is a global issue due to the existing climate change problem that reduces agricultural productivity and increases prices. It badly affects the yield, and active constituents of medicinal and aromatic plants, especially in newly reclaimed lands in desert areas. The Hibiscus sabdariffa L. is a remarkable crop known for its calyces to make a refreshing drink. It is in other food industries and has many healing effects. A split-plot field experiment was conducted on Hibiscus sabdariffa L. at Siwa Oasis, Egypt, during the 2018 and 2019 seasons for studying to reduce the harmful effect of heat stress on plants and yield improvement. Spraying with three salicylic acid concentrations was put to main plots as 0, 500, and 1000 mg/l and the number of sprays with Spirulina platensis algae extract was allotted to sub-plots and used as 0, 1 and 2 times in the season. Some quantity and quality parameters were under investigation. The significant highest increases in dry weight per plant, number of fruits per plant, dry yield of sepals per hectare and sepal's anthocyanin content were from the combination among spraying with salicylic acid at the concentration of 500 mg/l and spraying with blue green algae extract twice through the season. This treatment was helpful to decrease the high-temperature injury on growth through the summer months.